Structure and vascularization of the ventricular myocardium of Piaractus mesopotamicus and Clarias gariepinus (Teleostei) - Simoes, K.; Vicentini, C. A.; da Cruz, C.; Benetti, E. J. (Blackwell Wissenschafts Verlag Gmbh, 1999)
The structural characteristics of the ventricular myocardium and the arterial distribution of the ventricular wall were studied in two freshwater teleost fish species (Piaractus mesopotamicus and Clarias gariepinus). The ventricular myocardium consists of two distinct layers, an external compact layer and an internal spongy layer. In Piaractus mesopotamicus the compact layer contains fibres with an external longitudinal arrangement and an internal circular arrangement. The arterial vascularization of the compact layer is provided by subepicardial vessels and their ramifications in both species.